2019
DOI: 10.3390/s19030577
|View full text |Cite
|
Sign up to set email alerts
|

Monolithic Microwave-Microfluidic Sensors Made with Low Temperature Co-Fired Ceramic (LTCC) Technology

Abstract: This paper compares two types of microfluidic sensors that are designed for operation in ISM (Industrial, Scientific, Medical) bands at microwave frequencies of 2.45 GHz and 5.8 GHz. In the case of the first sensor, the principle of operation is based on the resonance phenomenon in a microwave circuit filled with a test sample. The second sensor is based on the interferometric principle and makes use of the superposition of two coherent microwave signals, where only one goes through a test sample. Both sensors… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 29 publications
0
21
0
Order By: Relevance
“…Low-temperature cofired ceramic (an aluminum oxide-based material) can be employed to fabricate microfluidic platforms [ 17 , 32 ]. The properties that recommend ceramics for microchips are their unique surface chemistry, good resistance to corrosive environments, and good stability at high temperatures [ 17 , 25 ].…”
Section: Fabrication Of Microfluidic Devicesmentioning
confidence: 99%
“…Low-temperature cofired ceramic (an aluminum oxide-based material) can be employed to fabricate microfluidic platforms [ 17 , 32 ]. The properties that recommend ceramics for microchips are their unique surface chemistry, good resistance to corrosive environments, and good stability at high temperatures [ 17 , 25 ].…”
Section: Fabrication Of Microfluidic Devicesmentioning
confidence: 99%
“…Compared with the reported LTCC microfluidic biosensor based on electrochemical methods, absorption photometry, microwave resonators, and capacitive sensing with interdigitated capacitors (IDCs) [ 39 , 40 , 41 , 42 , 43 ], we provided a wireless detection method without using fluorescent labeling, complex chemical reactions, and wire connections. Moreover, the designed sensor was more sensitive to changes in the permittivity of liquids within a wide range of permittivity than most of the reported microwave electromagnetic sensors.…”
Section: Resultsmentioning
confidence: 99%
“…Another example is the microstrip resonator, made on DuPont 951 PX LTCC [ 101 ]. The resonator was designed with the microchannel placed in the cavities of the split-ring resonator.…”
Section: Areas Of Microwave Applications In the Microfluidicsmentioning
confidence: 99%
“…After the measurements, it was observed that changes in the volume of ethanol in deionized water, as well as changes in dopamine content, affected the response of the sensor. In [ 101 ], another device was presented. Such a module was also made using the LTCC material as a substrate, but the microwave circuit consisted of the Wilkinson divider, the symmetric transmission lines, and the rat-race hybrid, similar to the solution shown in [ 49 ].…”
Section: Areas Of Microwave Applications In the Microfluidicsmentioning
confidence: 99%
See 1 more Smart Citation